2003
DOI: 10.1258/000456303321610538
|View full text |Cite
|
Sign up to set email alerts
|

An audit of the laboratory interpretation of growth hormone response to insulin-induced hypoglycaemia in the assessment of short stature in children

Abstract: Introduction Measurement of serum growth hormone (GH) concentration in response to insulin-induced hypoglycaemia remains an important investigation in the assessment of pituitary disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 8 publications
(10 reference statements)
0
6
0
Order By: Relevance
“…For GH, Andersson et al (5) illustrated how laboratories transfer cutoffs to new methods while ignoring known biases in the process, in effect, sustaining historical databases that are of little diagnostic merit. Ellis et al (6) illustrated the impact of using out-of-date cutoffs with the outcome of an interpretive exercise for an insulin tolerance test for GH deficiency in which 10% of 52 laboratories would have reported an "equivocal response" or "partial deficiency," even though the mean peak GH level was 32.8 mU/ liter. The use of a variety of factors for converting g/liter to mU/liter is an additional unnecessary complexity that hinders data interpretation.…”
mentioning
confidence: 99%
“…For GH, Andersson et al (5) illustrated how laboratories transfer cutoffs to new methods while ignoring known biases in the process, in effect, sustaining historical databases that are of little diagnostic merit. Ellis et al (6) illustrated the impact of using out-of-date cutoffs with the outcome of an interpretive exercise for an insulin tolerance test for GH deficiency in which 10% of 52 laboratories would have reported an "equivocal response" or "partial deficiency," even though the mean peak GH level was 32.8 mU/ liter. The use of a variety of factors for converting g/liter to mU/liter is an additional unnecessary complexity that hinders data interpretation.…”
mentioning
confidence: 99%
“…6 This may contribute to the widespread confusion regarding appropriate cut-offs for GH deficiency. 7,8 We have shown that the relationship between assays remains constant for values <20 μ g/L (60 mU/L) even after stimulation. The negative bias of the recalibrated assay at concentrations >20 μ g/L (60 mU/L) should not compromise the clinical interpretation of results.…”
Section: Discussionmentioning
confidence: 89%
“…Unfortunately, these prerequisites cannot be fulfilled, as GH is heterogeneous, the biological activity of various GH forms is not constant, differences exist in the specificity of assays and several reference materials are in use. Consequently, method-based differences exist in clinical cut-off values used for the confirmation of diagnosis of GH deficiency [13] and for the diagnosis and follow-up of treatment balance in acromegalic patients [23] A recent audit of the laboratory interpretation of GH results in an insulin stress test showed that some laboratories were using cut-off concentrations that were unrelated to the bias of their GH assay [24]. Frequent changes of assay method may also confuse the clinician and lead to incorrect interpretation.…”
Section: Discussionmentioning
confidence: 99%